Primary cutaneous CD 30 (+) ALK (-) anaplastic large cell lymphoma with dermoscopic findings: a case report - Tugba Kevser Ustunbas Uzuncakmak; Necmettin Akdeniz; Ayse Serap Karadag; Secil Taskin; Ebru Itır Zemheri; Giuseppe Argenziano (Mattioli1885, 2017)
Primary cutaneous CD 30 (+) anaplastic large cell lymphoma (PCALCL) is a rare and indolent type of cutaneous T cell lymphoma, which usually presents as an asymptomatic solitary firm nodule that rapidly grows and often ulcerates without any systemic involvement.  A 64-year-old female presented to our outpatient clinic with a one-year history of multiple pink nodular lesions on the chest, back and gluteal regions. Dermoscopic examination of the nodular lesions revealed pink-to-yellow structureless areas and arborizing-to-polymorphous vessels. Histopathologic examination was consistent with CD30 (+) anaplastic large cell lymphoma. Systemic involvement was not detected. Local radiotherapy for large nodules and surgical excision for small nodules were performed. The large nodules had totally regressed after 10 sessions of radiotherapy.